The AMINO experiment: exposure of amino acids in the EXPOSE-R experiment on the International Space Station and in laboratory. Issue 1 (January 2015) - Bertrand, Marylène; Chabin, Annie; Colas, Cyril; Cadène, Martine; Chaput, Didier; Brack, Andre; Cottin, Herve; Westall, Frances; Horneck, Gerda; Panitz, Corinna; Martins, Zita
Abstract In order to confirm the results of previous experiments concerning the chemical behaviour of organic molecules in the space environment, organic molecules (amino acids and a dipeptide) in pure form and embedded in meteorite powder were exposed in the AMINO experiment in the EXPOSE-R facility onboard the International Space Station. After exposure to space conditions for 24 months (2843 h of irradiation), the samples were returned to the Earth and analysed in the laboratory for reactions caused by solar ultraviolet (UV) and other electromagnetic radiation. Laboratory UV exposure was carried out in parallel in the Cologne DLR Center (Deutsches Zentrum für Luft und Raumfahrt). The molecules were extracted from the sample holder and then (1) derivatized by silylation and analysed by gas chromatography coupled to a mass spectrometer (GC–MS) in order to quantify the rate of degradation of the compounds and (2) analysed by high-resolution mass spectrometry (HRMS) in order to understand the chemical reactions that occurred. The GC–MS results confirm that resistance to irradiation is a function of the chemical nature of the exposed molecules and of the wavelengths of the UV light. They also confirm the protective effect of a coating of meteorite powder. The most altered compounds were the dipeptides and aspartic acid while the most robust were compounds with a hydrocarbon chain. The MS analyses document the products of reactions, such as decarboxylation and decarbonylation of aspartic acid, taking place after UV exposure. Given the universality of chemistry in space, our results have a broader implication for the fate of organic molecules that seeded the planets as soon as they became habitable as well as for the effects of UV radiation on exposed molecules at the surface of Mars, for example.